Asphalt 60/70 Penetration Analysis of AC/BC Mixture With the Addition of Ethylene Vinyl Acetate (EVA) As Asphalt Raw Material - Siregar, Zulkifli; Asfiati, Sri; Gultom, Mhd. Husin (ASTONJADRO, 2023)
This study was conducted to determine how much influence EVA (Ethylene Vinyl Acetate) added to Laston AC-BC has on Marshall characteristic values. The Marshall test carried out will produce stability values at the optimum asphalt conditions that meet the 2018 Highways specifications. The stability value will be used to analyze changes in the characteristics of the Laston AC-BC (Asphalt Concrate – Binder Course) mixture after adding a mixture of EVA (Ethylene Vinyl Acetate) . To determine an aggregate gradation in the AC-BC mixed layer, coarse aggregate is used in the form of crushed stone with a maximum size of ” while for fine aggregate it is a mixture of crushed stone, stone ash and sand. The additive or modifier used is EVA (Ethylene Vinyl Acetate) polymer. Next, to obtain good asphalt concrete, the gradation of the aggregate must meet the general specifications of Bina Marga 2018 which have been determined through SNI-ASTM-C136-2012. In making the test object, ± 1200 gram of aggregate and asphalt are needed so that the specified height of the test object will be produced. Through the analysis of the aggregate sieve, the weight of the aggregate required for the test object can be calculated. Modification of asphalt with EVA aims to determine the stiffness and properties of asphalt in resisting loading with a certain penetration value so as to produce a Penetration Index value which will affect the characteristics of asphalt against weather changes. Research and knowledge related to the addition of a mixture of EVA (Ethylene Vinyl Acetate) to asphalt can be further developed so that it can be implemented on types of road pavements with higher traffic density conditions.